Sialidase and Sialyltransferase Inhibitors: Targeting Pathogenicity and Disease - Bowles, William H. D.; Gloster, Tracey M. (Frontiers in Molecular Biosciences, 2021)
Sialidases (SAs) and sialyltransferases (STs), the enzymes responsible for removing and adding sialic acid to other glycans, play essential roles in viruses, bacteria, parasites, and humans. Sialic acid is often the terminal sugar on glycans protruding from the cell surface in humans and is an important component for recognition and cell function. Pathogens have evolved to exploit this and use sialic acid to either ‘cloak’ themselves, ensuring they remain undetected, or as a mechanism to enable release of virus progeny. The development of inhibitors against SAs and STs therefore provides the opportunity to target a range of diseases. Inhibitors targeting viral, bacterial, or parasitic enzymes can directly target their pathogenicity in humans. Excellent examples of this can be found with the anti-influenza drugs Zanamivir and Oseltamivir, which have been used in the clinic for over two decades. However, the development of resistance against these drugs means there is an ongoing need for novel potent and specific inhibitors. Humans possess 20 STs and four SAs that play essential roles in cellular function, but have also been implicated in cancer progression, as glycans on many cancer cells are found to be hyper-sialylated. Whilst much remains unknown about how STs function in relation to disease, it is clear that specific inhibitors of them can serve both as tools to gain a better understanding of their activity and form the basis for development of anti-cancer drugs. Here we review the recent developments in the design of SA and ST inhibitors against pathogens and humans.